THE RELATIONSHIP OF MOTIVATION PROVISION BY CLINICAL INSTRUCTOR WITH STUDENT'S READINESS TO EXPERIENCE CLINICAL PRACTICE IN HOSPITAL - Gracia Herni Pertiwi; Made Ermayani (NurseLine Journal, 2017)
Motivation is a driving force that affects a person's readiness to start doing a series of activities in a behavior. The unpreparedness and anxiety of nursing students during clinical practice is due to the fact that students have no previous experience or description of clinical practice. Almost all students have anxiety when they do the first practice in the hospital, the students become desperate and helpless. Another cause of anxiety is student concern about the possibility of endangering patients due to their lack of knowledge. The purpose of this research was to identify the corelation between provision of motivation by clinical instructor and student's readiness to experience clinical practice in hospital. The research method was analytical descriptive. The sampling technique was simple random sampling conducted to the second grade students who practice in hospital. The sample consisted of 83 respondents. The questionnaire used in this study included questionnaire of motivation provision by the clinical instructor and questionnaire of student's readiness to experience clinical practice in hospital by using likert scale. Data were analyzed by chi square test with significance value of p <0.05. The results showed that there was a correlation between the provision of motivation by clinical instructor and student's readiness to experience clinical practice in hospital (p = 0.008). Motivation by clinical instructor helps improve students' readiness to perform clinical practice. Clinical instructor should optimize the motivation for students. Giving good motivation to the students is not only limited to feedback for the competence that has been done but also creates a pleasant atmosphere of guidance and does not cause tension so that student anxiety level can be minimized.